Changes in the synganglion of Rhipicephalus sanguineus (Latreille,. 1806) (Acari: Ixodidae) female ticks exposed to permethrin: An ultrastructural overview - Roma, Gislaine Cristina [UNESP]; Camargo Mathias, Maria Izabel [UNESP]; Nunes, Pablo Henrique [UNESP]; Bechara, Gervasio Henrique [UNESP] (Elsevier B.V., 2014)
This study performed the ultra-structural analysis of the changes caused by permethrin in the synganglion of semi-engorged Rhipicephalus sanguineus females, aiming to understand the toxic action of this substance at cellular level. The results showed that the neural lamella had its structure changed, allowing the influx of the toxic agent into the nervous tissue. The glial cells of the perineurium, as well as the neural cells of the cortex showed great changes, such as: irregular nuclei with chromatin margination, cytoplasmic vacuolation and degenerating mitochondria. These changes showed that the permethrin would be able to induce the degeneration of the synganglion through an atypical death process, involving apoptosis and autophagy. In addition, a dilated rough endoplasmic reticulum was observed in the neural cells, suggesting an intense synthesis of the hydrolytic enzymes that would be used in the processes of degradation of the damaged cellular structures (formation of lysosomes). The subperineurium and the neuropile also showed changes in their structures. Thus, it is suggested that permethrin is a dose-dependent compound able to impair the metabolism of the organism as a whole, once all the other organs and body structures are directly dependent of the neural control. The information obtained in this study can be used in the improvement of the control methods which use permethrin as active substance, helping in the creation of a really efficient acaricide product to fight this important urban plague. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Central nervous system; Synthetic product; Semi-engorged females; Neurotoxic action